Ventilation-perfusion mismatching in acute severe asthma: effects of salbutamol and 100% oxygen. Issue 4 (April 1989) - Ballester, E; Reyes, A; Roca, J; Guitart, R; Wagner, P D; Rodriguez-Roisin, R
Abstract : Ventilation-perfusion (VA/Q) relationships and gas exchange were studied by the multiple inert gas technique in 19 patients admitted to hospital with acute severe asthma (FEV1 41% predicted) before and during the administration of intravenous salbutamol, inhaled salbutamol, or 100% oxygen. Eight patients received a continuous intravenous infusion of salbutamol (4 micrograms/min, total dose 360 micrograms) and were studied before treatment, after 60 and 90 minutes of treatment, and one hour after treatment had been discontinued. Six patients had measurements before and 15 minutes after inhaling 300 micrograms salbutamol from a metered dose inhaler on two occasions (total dose 600 micrograms) and one hour after the last dose. Measurements were also made in five patients before and while they breathed 100% oxygen for 20 minutes. At baseline (fractional inspired oxygen (FiO2) 21%) all patients showed a broad unimodal (n = 10) or bimodal (n = 9) distribution of blood flow with respect to VA/Q. A mean of 10.5% of the blood flow was associated with low VA/Q units without any appreciable shunt. One of the best descriptors of VA/Q inequality, the second moment of the perfusion distribution on a log scale (log SD Q), was moderately high with a mean of 1.18 (SEM 0.08) (normal less than 0.6). Measures of VA/Q inequality correlated poorly with spirometric findings. After salbutamol the increase in airflow rates was similar regardless of the route of administration. Intravenous salbutamol, however, caused a significant increase in heart rate, cardiac output, and oxygen consumption (VO2); in addition, both perfusion to low VA/Q areas and log SD Q increased significantly. Inhaled salbutamol caused only minor changes in heart rate, cardiac output, VO2, and VA/Q inequality. Arterial oxygen tension (PaO2) remained unchanged during salbutamol administration, irrespective of the route of administration. During 100% oxygen breathing there was a significant increase in log SD Q (from 1.11 to 1.44). It is concluded that patients with acute severe asthma show considerable VA/Q inequality with a high level of pulmonary vascular reactivity. Despite similar bronchodilator effects from inhaled and intravenous salbutamol, VA/Q relationships worsened only during intravenous infusion. PaO2 remained unchanged, however, because the change in VA/Q relationships was associated with an increase in metabolic rate and cardiac output.